Preparation and characterization of commercial cold water fish gelatin-based composite film for packaging red tilapia (Oreochromis niloticus Linnaeus) - Golpira, Fatemeh (2015)
Food packaging is traditionally limited to protect the food from physical, biological and chemical deterioration before consumption. In the recent years, the production of ecofriendly natural polymers as packaging material has many attractions for food manufacturers. The natural biodegradable polymers are more preferred to non-biodegradable plastic packaging polymers, which cause the biological pollution. Gelatin is one of the most common types of packaging polymer derived from bovine and porcine sources. In recent years, gelatin from marine fish species has been introduced as an alternative to mammalian gelatin. Cold water fish skin gelatin show worse rheological properties, low stability, gelling and melting points in comparison with mammalian and warm water fish gelatin. Gelatin films also have good oxygen barrier properties, but possess poor water barrier. The main goal of this study was to improve the characteristics of gelatin from the cold water fish skin. The first objective was to investigate the effect of type and concentration of different polysaccharide gums (i.e. pectin (P), sodium alginate (SA), and karaya gum (KG), 1% and 2% w/v) as well as glycerol content (30% and 40%) on the characteristics of fish skin gelatin film. The differences among different films (FSG, FSG-P, FSG-SA and FSGKG) were assessed by determining the physical, mechanical, barrier, microstructure, and thermal properties. The second objective was to compare the efficiency of the most desirable composite film and two commercial films on the quality and shelf life of the red tilapia fish fillets. The efficiency of the most desirable composite films and two commercial films (i.e. low- and high density polyethylene, LDPE and HDPE) were compared by assessing the moisture content, pH, aw, colour (L*, a* and b*), texture properties (hardness, cohesiveness, springiness), rancidity degree and microbial quality of red tilapia fish fillets in the fresh form and after 28 days storage at 4 °C. The addition of polysaccharide gum to the native fish skin gelatin led to improve its melting point, tensile strength (TS), and barrier properties (i.e. water vapour and oxygen). The tensile strength (TS) and melting point were decreased; while the elongation at break (EAB), water vapour permeability (WVP), and oxygen permeability were increased by increasing the percentage of glycerol (as a plasticizer) in the film formulation. Also, FSG based composite films containing 2% karaya gum, sodium alginate, and pectin decreased solubility from 99% to 32%, 39%, and 46%, respectively at 30% glycerol content. The composite film containing 2% polysaccharides gum (especially sodium alginate and karaya gum) along with 30% glycerol had the most desirable characteristics among all composite films. In the present study, karaya gum and pectin induced the most and least desirable effect on the characteristics of FSG film. Among all samples, the composite films (FSG-KG and FSG-SA) containing 30% glycerol had the most desirable characteristics in terms of physical-, mechanical- and barrier properties. Therefore, they were chosen for wrapping red tilapia fish and storage study. For shelf life testing and storage study, the tilapia fish fillets were wrapped with the most desirable composite films and two commercial films (LDPE and HDPE) and stored for 28 days at 4 °C. All wrapped samples were analyzed by the interval of 7 days in terms of microbial quality, physical and chemical characteristics, and texture. TBA of fish fillet wrapped with commercial films showed the highest changes (0.03-0.99); while FSG-KG wrapped fish fillet had the lowest TBA changes (0.03-0.36) among all samples. Tilapia fish fillets wrapped with the composite films had lower colour and texture changes than the samples wrapped with commercial films. In this study, the composite films (FSG-KG and FSG-SA) more efficiently retarded the microbial growth of red tilapia fish than the native FSG film and target commercial films (i.e. LDPE and HDPE).